Comparative Evaluation of Compost, Wheat Straw and Sawdust on Soil Structural Stability, Plant Available Water and Sorghum (Sorghum biocolor L.) Yield: Influence of organic amendments on soil properties and yield - Shaheen, Aqila; Munsaf, Saba; Khaliq, Abdul; Zahid, Nafeesa (Proceedings of the Pakistan Academy of Sciences: B. Life and Environmental Sciences, 2021)
The decreased soil structural stability with a resultant reduction in soil porosity, availability of water and nutrients has declined the crop yield. Compost, wheat straw and sawdust, the organic wastes can be effectively used as soil amendments to improve soil structure, porosity and water holding capacity and the crop yield. The study was conducted in randomized complete block design (RCBD) and three types of amendments i.e. compost (CM), wheat straw (WS) and sawdust (SD) were applied at three rates of 0, 4 and 8 t ha-1. The higher sorghum growth was at 8 t ha-1, however, 4 t ha-1 also indicated statistically comparable trend. The highest grain yield of 1357 kg ha-1 and 1374 kg ha-1 was observed in amended soils and type of amendments showed statistically (P≤ 0.05) similar yield. The water contents at field capacity (35.4 %), wilting point (22.5 %) and plant available water (13.25 %) were higher in WS 8 t ha-1 amendment. The higher soil structure stability of 90.78 % was observed in WS with rates of 8 t ha-1. The crop residue WS 8 t ha-1 have the potential to increase soil water retion and soil structure stability as well. The CM, WS and SD amendments significantly improved organic matter (OM), porosity, nitrogen ( N) and phosphorus (P) of soil in 4 and 8 t ha-1 than control. The low bulk density (BD) of 1.07 g cm-3 was in WS 8 t ha-1 and the lower pH was recorded in CM 8 t ha-1. The study showed that all three types of amendments (CM, WS and SD) at 4 and 8 t ha-1 rates have potential to improve the soil structural stability, plant available water and yield of grain sorghum.